2019
DOI: 10.1177/1533033819894331
|View full text |Cite
|
Sign up to set email alerts
|

Methylene Blue–Based Near-Infrared Fluorescence Imaging for Breast Cancer Visualization in Resected Human Tissues

Abstract: Breast-conserving surgery is facing the challenge of objective tumor margin identification intraoperatively. Near-infrared fluorescence imaging would be an ideal approach to visualize tumor margins during surgeries. In this preliminary study, the feasibility of methylene blue–based near-infrared fluorescence imaging technique for breast cancer detection was assessed in resected human breast specimens after breast cancer surgeries. Thirty patients with breast cancer scheduled for surgical treatment were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 35 publications
(45 reference statements)
1
45
0
Order By: Relevance
“…Then, 17% of BCS specimens had fluorescing surfaces indicative of positive margins. Similar uptake characteristics were observed in another independent study by Zhang et al where an in-house built NIR-FI system was used on 30 breast cancer patients with (n = 10) and without (n = 20) chemotherapy [93]. The authors observed that 80% of specimens from patients without chemotherapy and 30% from patients with chemotherapy showed sufficient contrast suggesting the unsuitability of MB for patients receiving preoperative chemotherapy.…”
Section: Fluorescence Imaging With Medically Approved Dyessupporting
confidence: 82%
“…Then, 17% of BCS specimens had fluorescing surfaces indicative of positive margins. Similar uptake characteristics were observed in another independent study by Zhang et al where an in-house built NIR-FI system was used on 30 breast cancer patients with (n = 10) and without (n = 20) chemotherapy [93]. The authors observed that 80% of specimens from patients without chemotherapy and 30% from patients with chemotherapy showed sufficient contrast suggesting the unsuitability of MB for patients receiving preoperative chemotherapy.…”
Section: Fluorescence Imaging With Medically Approved Dyessupporting
confidence: 82%
“…1 FMI with NIR fluorophores has added to surgeons' armamentarium to achieve negative margins and has been successfully implemented in glioma, breast cancer, and ovarian cancer. 2,8,9 Prior studies demonstrated that ICG failed to localize head and neck neoplasms and their margins during TORS. 4 However, our group demonstrated that SWIG imaging with the VisionSense Iridium TM can be used for intraoperative visualization of head and neck tumors and identification of regional metastasis to aid surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, some nodules cannot be found during the operation. 18 The ultrasound probe can be placed directly above the nodule during the ultrasound-guided minimally invasive biopsy of breast nodules. The surgical puncture point is usually located next to the probe.…”
Section: Discussionmentioning
confidence: 99%